Analisis Strategi Promosi Universitas Muhammadiyah Buton di Aplikasi Media Sosial Tiktok - Sinli Samlaw; Ansar Suherman; Wa Nur Fida (BUDGETING : Journal of Business, Management and Accounting, 2023)
The Role of social media, especially TikTok, as a promotional tool for Muhammadiyah Buton University. In the digital era, online promotion through social media has become an effective solution to enhance the appeal of higher education institutions. With the extensive usage of the TikTok app, universities are competing to utilize it as a promotional channel. Challenges arise in content variation, requiring creative strategies to maintain prospective students' interest. This research aims to analyze the extent of Muhammadiyah Buton University's Promotion Strategy in attracting new students through the TikTok application. This study employs a qualitative approach to comprehend the phenomenon of TikTok's social media usage as a promotional tool for Muhammadiyah Buton University. It integrates marketing communication theory and uses and gratification theory. The research takes place at the Muhammadiyah Buton University campus. Research informants involve the Public Relations staff (UM Buton) and new students from the 2023 intake following the TikTok account (UM Buton). The research findings discuss Muhammadiyah Buton University's Promotion Strategy on the TikTok Application. Leveraging the TikTok trend, Muhammadiyah Buton University creates engaging content that captures prospective students' attention. Interview results indicate that using TikTok as a promotional medium is highly effective, with content successfully making it to the For You Page (FYP). New students obtain a lot of information about Muhammadiyah Buton University through TikTok, demonstrating the success of the promotional strategy. TikTok content from Communication Science students successfully attracts prospective students, providing a unique insight into Muhammadiyah Buton University's strengths. Despite the Public Relations team facing Human Resource challenges, particularly a lack of staff, this was overcome by involving student contributions in creating promotional content. Students responded positively to the content, noting that TikTok promotion helped them better understand Muhammadiyah Buton University's programs and activities. The TikTok Promotion Strategy successfully raises awareness of Muhammadiyah Buton University and has a positive influence on new student enrollment. Although there were some less positive views regarding the lack of content depicting the campus atmosphere, TikTok promotion managed to create significant attraction and positive impact. Interviews with new students indicate that TikTok content was effective in influencing their decision to join Muhammadiyah Buton University. The success of the promotional strategy involves creativity in content, focusing on relevant information, and student involvement. Overall, TikTok promotion creates a positive and convincing image for prospective students. People from the community who provided services at the Bengkulu City Manpower Office. The data analysis technique used is an interactive model. Checking the validity of the data is done by triangulation of sources and methods.The results of the study show that the implementation of public service quality in Industrial Relations Dispute Settlement services at the Bengkulu City Manpower Office is seen from the aspects of Reliability, Responsiveness, Assurance, Empathy, Tangibles. (1) The community is satisfied with the services provided at the Industrial Relations Dispute Settlement Service Section at the Bengkulu City Manpower Office in terms of reliability, reliability in the accuracy of the service process (2) employees who are ready to help people who need special services, people who minimal information, with officers who convey information by communicating well with the community. (3) Security at the Bengkulu City Manpower Service Office has provided good service quality, by providing a sense of security to people who perform public services, and ensuring secure data storage. (4) The Bengkulu City Manpower Office provides an aspect of empathy with a pleasant impression, this can be seen from the attitude of explaining as clearly as possible regarding service procedures and applicable SOPs. (5) The tangibles aspect of the service room and waiting room is sufficient, with waiting chairs and tables, but the mediation room which is not spacious plus there is a table inside sometimes makes the room cramped when there are many people in it. Keywords: Muhammadiyah Buton University, Promotion Strategy, TikTok Application